Mechanistic Insights into Phenol Oxidation by a Copper(II) Complex of a Pyridine‐ and Amide‐Containing Copolymer in an Aqueous Medium. Issue 3 (7th November 2014) - Lykourinou, Vasiliki; Ming, Li‐June
Abstract: A Cu II complex of a pyridine‐ and amide‐containing copolymer (Cu‐P1 ) exhibits effective activity toward phenol hydroxylation in 50 % aqueous methanol solution at apparent pH 8.0 and 25 °C. The complex shows significant first‐order rate accelerations of 4.2 × 10 5 and 1.4 × 10 5 relative to phenol autoxidation in air and in the presence of 20 mM H2 O2, respectively. The reaction mechanisms with H2 O2 and air are different on the basis of (a) the different activity profiles for Cu binding, (b) the different deuterium kinetic isotope effects (2.8 in 20 mM H2 O2 and 1.2 aerobically), and (c) the formation of a dinuclear substrate–(Cu‐P1 ) complex with H2 O2 but a mononuclear one aerobically. The mechanism in the presence of H2 O2 is consistent with that of the type‐3 dicopper tyrosinase. Although oxidized di‐Cu II tyrosinase can only use H2 O2 for phenol hydroxylation, Cu II ‐P1 can use either air or H2 O2 for this process. The studies herein introduce a versatile chemical system for the further exploration of Cu–oxygen chemistry and other types of metal‐centered chemistry and for the aerobic degradation of aromatic compounds in environmental and green chemistry. Abstract : A Cu II complex of a pyridine‐ and amide‐containing copolymer catalyzes phenol hydroxylation/oxidation in aqueous methanol at pH 8.0 and 25 °C. First‐order rate accelerations by factors of 4.2 × 10 5 and 1.4 × 10 5 and deuterium kinetic isotope effects of 2.8 and 1.2, respectively, were observed with and without H2 O2 . The results suggest that different mechanisms apply for oxidation by O2 and H2 O2 .